ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Mebel Madina di Kota Banjarnegara) - Afwan, Mukhammad Teguh; Santosa, Suryono Budi (Diponegoro Journal of Management, 2020)
This research was based on the phenomenon of the decline in sales that had occurred in madina furniture in the last two years, in 2016 and 2017. Even though the marketing business since 2005 has never experienced a decline in sales. The decline in sales was due to many market competitors. This study aims to analyze product quality, price perception, service quality on brand image and its impact on Madina furniture purchasing decisions. The population used in the study is all consumers who had ever purchases transaction of products in Madina Mebel store, where respondents in Banjarnegara. The samples of this study is 125 respondents. The method of collecting data through questionnaires. This study used analytical technique of structural Equation Modeling (SEM) analysis technique of AMOS 22.0 analysis tool. The results showed that product quality have positive and significant effect to brand image, price perception have positive and significant effect to brand image, service quality have positive and significant effect to brand image, and product quality have positive and significant influence to purchase decision, and significant to purchase decision, service quality have positive and significant effect to purchasing decision, brand image have positive and significant effect to purchasing decision. All variables in the study have positive and significant impacts so that Madina Furniture can focus on improving product quality, price perception, service quality and store brand image in increasing purchasing decisions.